Survey of recognition and treatment of at‐risk mental state by Japanese psychiatrists. Issue 6 (23rd March 2018) - Tsujino, Naohisa; Tagata, Hiromi; Baba, Yoko; Kojima, Akiko; Yamaguchi, Taiju; Katagiri, Naoyuki; Nemoto, Takahiro; Mizuno, Masafumi
Abstract : Aim: The importance of early intervention in psychiatry is widely recognized among psychiatrists. However, it is unknown whether precise knowledge of at‐risk mental state has been disseminated. With this survey, we aimed to reveal how Japanese psychiatrists diagnose patients with at‐risk mental state and prescribe treatment strategies for them. Methods: Using fictional case vignettes, we conducted a questionnaire survey of psychiatrists ( n = 1399) who worked in Tokyo. We mailed study documents to all eligible participants in November 2015 with a requested return date in December. Results: Two hundred and sixty (19.3%) psychiatrists responded to the survey. Their correct diagnosis rates for the patients in the at‐risk mental state vignettes were low (14.6% for the vignette describing at‐risk mental state with attenuated positive symptom syndrome; 13.1% for the vignette describing at‐risk mental state with brief intermittent psychotic syndrome). Many psychiatrists selected pharmacotherapy and antipsychotics to treat patients in the at‐risk mental state vignettes. The psychiatrists who correctly diagnosed patients in the at‐risk mental state vignettes had significantly fewer years of clinical psychiatric experience than did those who diagnosed them as having a non‐at‐risk mental state (12.5 years vs 22.7 years for the vignette describing at‐risk mental state with attenuated positive symptom syndrome, P < 0.01; 14.3 years vs 22.2 years for the vignette describing at‐risk mental state with brief intermittent psychotic syndrome, P < 0.01). Conclusion: This study suggests that precise knowledge of at‐risk mental state has not been disseminated among Japanese psychiatrists.